IDEALITAS DAN REALITAS KEMAMPUAN GURU MI/SD DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN TEMATIK - Nurkhairina; Hidayatullah, Agus; Rosyidah, Neneng Aida; Noviyanti (Ta'dibiya, 2023)
Learning in the 2013 curriculum uses integrated thematic learning. This causes teachers to master and carry out thematic learning well. However, there are many problems that occur, then what is the ideal of the teacher in carrying out thematic learning. This research intends to know and explain in detail about the ideals and reality of MI/SD teachers' abilities in implementing thematic learning. The results of this study are; Ideally the teacher in this thematic learning is to provide meaningful teaching and experiences to students. Not only that, a teacher in addition to being a professional educator, is also an educator, teacher, mentor, director, assessor, and evaluator of students, especially in early childhood education and basic education. There are two factors that impact on the obstacles for teachers to implement, namely: internal factors and external factors. Teachers are still lacking in comprehensive education and training; teachers also still find it difficult to integrate tactics in the learning theme.